STUDI METODE PELAKSANAAN PONDASI JEMBATAN KAYU DI SEI KARAU, KABUPATEN BARITO TIMUR (Study of the Implementation Methods of Wood Bridge in Sei Karau, East Barito District) - Maretina Maretina Eka Sinta; Jaro Jaro Lelond Tuah, S.T (Huma Tabalien Jurnal (HTJ) Teknik Sipil, 2021)
Based on its function, a bridge is a structure that is made as an intermediary or link to cross / cross ravines or obstacles such as rivers, railroads or roads, so to connect the city of Ampah which is split by the Karau river, a bridge is needed. The object of research is a wooden bridge made by the Dutch colonial in 1929 which still stands firmly and can be used today, so to find out the method of implementation at the time of building the bridge, as well as to see the development of current implementation methods and resources, research was conducted to know the implementation method specifically for the installation of the foundation to find out the implementation technique and the equipment used. The research method used includes: (1) preliminary survey, (2) data collection and data analysis, (3) reconstruction of implementation methods, (4) delineation of reconstructed results. The results of the research study show that all stages of implementation use simple methods using simple mechanical equipment as well. In the case of the installation of the foundation, the executor takes into account the placement of the point where the foundation is laid. The soil bearing capacity is estimated in a simple way. Keywords: History, Implementation Methods / Terms of Reference, Resources